Famous for a living : a novel [large type] - Ferguson, Melissa (Assistant professor) (Center Point Large Print, 2023)
"When her business partner is accused of serious financial crimes, superstar influencer Cat Cranwell -- an engineered marvel of beauty, energy, and fun -- falls from her penthouse perch. Desperate to get away from the online trolls and paparazzi documenting her disgrace, Cat accepts her uncle's offer to work with him in Kannery National Park, Montana. About as far as possible from life as she's known it. Cat's world shifts from the swirling haze of likes and comments to literal blizzards of frostbite temperatures and waist-deep snow. In place of negotiating brand deals she finds herself negotiating at the edge of a frozen lake with her die-hard Polar Bear Plunge coworkers. Instead of padding through the marble kitchen of her Manhattan loft, she's sharing a tent-sized cabin with a roommate eager to bond like characters in sitcoms. But something curious is also happening in this overwhelming breath of fresh air as she reacquaints with the most honest parts of herself and begins to ask the hard questions. Can Cat love herself with, and without, the world watching? Then there's that other tiny problem -- she's falling for Zaiah, the ruggedly handsome Park Ranger -- and he hates anything remotely connected to social media, quite possibly her included."--